FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AGRESIVITAS PAJAK DENGAN KOMITE AUDIT SEBAGAI PEMODERASI - Sekar Rani Arum Sari; Achmad Badjuri (JURNAL ILMIAH EDUNOMIKA, 2023)
The purpose of this study was to gain knowledge based on the facts and data obtained validity and reliably regarding wheter there is an influence of financial factors, including firm size, leverage, profitability, and audit committee as moderating variable in Manufacturing Sector Companies listed on the Indonesia Stock Exchange (BEI) 2019-2021. The research sample is filtered out to 161 sample data. The research method used is quantitative research with multiple regression analysis and Moderated Regression Analysis (MRA). Based on the results of this study indicate that leverage positively significant influences tax aggressiveness, but firm size and profitability has no effect on tax aggressiveness. The audit committee can moderate the influence of leverage on tax aggressiveness, but cannot moderate the relationship of firm size and profitability on tax aggressiveness.